Sosialisasi Bela Diri Shorinji Kempo Pada Remaja Dan Pemuda Desa Pulubala Kabupaten Gorontalo - Lamusu, Zulkifli A. (-, 2025)
This community service activity aims to introduce Shorinji Kempo martial arts to teenagers and young adults in Pulubala Village, Gorontalo Regency. Shorinji Kempo is a modern martial art originating from Japan that integrates physical, mental, and spiritual aspects into its training. This outreach programme is designed as an educational initiative to shape the character of the younger generation through a martial arts approach focused on values such as discipline, responsibility, and self-control. The methods used in this activity include lectures, interactive discussions, demonstrations of basic techniques, and hands-on practice by participants. The implementation of the activity involved collaboration between the academic team, the village government, and local participants. The results of the activity showed an increase in participants' understanding of the values and basic techniques of Shorinji Kempo, as well as growing interest in participating in further training. The positive response from participants reflects the great potential for the development of martial arts communities at the village level, which not only function as training centres but also as means of character building and sports achievement. This activity also strengthens the role of the Tri Dharma Perguruan Tinggi in the field of community service. The short-term impact, in the form of increased awareness among participants of the importance of martial arts as a productive activity, has been evident through post-activity evaluations and reflections. Meanwhile, long-term impacts are expected to materialise in the form of dojo establishment and sustained development for the younger generation in the village. Thus, this socialisation activity not only serves as a means of disseminating martial arts knowledge but also becomes an integral part of building healthy, resilient, and character-driven human resources.